Respuesta :

Hagrid
We can solve this by using the formula:
(x, y) (x + a, y + b) = (5,-4) (-2,1)

So, plugging in the values and solving for a and b,
5 + a = -2
a = -8

-4 + b = 1
b = 5

Therefore, the translation is
(x,y) (x - 8, y +5)

Answer:

The required algebraic rule of translation is [tex](x,y)\rightarrow (x-7,y+5)[/tex].

Step-by-step explanation:

The coordinates of a point are C(5, –4) and the coordinates of image are C’(–2, 1).

[tex]C(5,-4)\rightarrow C'(-2,1)[/tex]           .... (1)

Let the algebraic rule of translation is

[tex](x,y)\rightarrow (x+a,y+b)[/tex]           .... (2)

From (1) and (2) we get

[tex]x=5,y=-4[/tex]

[tex]x+a=-2[/tex]

[tex]5+a=-2[/tex]

[tex]a=-2-5[/tex]

[tex]a=-7[/tex]

The value of a is -7.

[tex]y+b=1[/tex]

[tex]-4+b=1[/tex]

[tex]b=1+4[/tex]

[tex]b=5[/tex]

The value of b is 5.

The algebraic rule of translation is

[tex](x,y)\rightarrow (x-7,y+5)[/tex]

Therefore the required algebraic rule of translation is [tex](x,y)\rightarrow (x-7,y+5)[/tex].